Neoliberalism and Working-Class Resistance in British Columbia: The Hospital Employees' Union Struggle, 2002-2004 - Camfield, David (Labour/Le Travail)

(untitled) (Canadian Committee on Labour History, 2006)
IN BRITISH COLUMBIA in the spring of 2004, over 40,000 hospital and long-term care facility workers, mostly members of the Hospital Employees Union [HEU], struck to defend their jobs and services against attacks from an aggressive neoliberal government and employers. This strike was distinguished by the social composition of the workforce, the fact that heu had one of the more left-wing leaderships in the Canadian labour movement, and the determination of the strikers to persevere even in the face of back-to-work legislation. HEU's resistance evoked an unusual degree of support that took the form of active solidarity rather than just passive sympathy. The BC labour leadership was pushed towards a confrontation of the kind that the existing regime of industrial legality was designed to prevent. This article identifies the systemic causes of the BC health care strike in public sector restructuring and the building of a lean state, explores its background, traces its trajectory, and explains and assesses its outcome. This strike highlights the significance of the character of the contemporary labour officialdom as a social layer whose conditions of existence lead it to usually oppose forms of collective action outside the bounds of industrial legality.